2021
DOI: 10.1007/s11356-021-17259-y
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced effect of biochar on leaching vanadium and copper from stone coal tailings by Thiobacillus ferrooxidans

Abstract: Among the many extraction technologies for recovering metal resources from tailings, bioleaching technology is gradually showing its momentum. In our research, the enhanced effect of biochar on the bioleaching of stone coal tailings by Thiobacillus ferrooxidans (T. ferrooxidans) has been explored. In the static bioleaching experiment for 10 days, the leaching rate of vanadium (V) and copper (Cu) increased by 26.8% and 21.0% respectively after adding 5 g/L biochar. The dynamic bioleaching experiment further ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Yang, Chen [78] found that with the addition of Fe 3+ , the rate and efficiency of jarosite bio-dissolution can be significantly accelerated and improved. Dong, Chong [81] explored the enhanced effect of biochar on the bioleaching of stone coal tailings by At. ferrooxidans.…”
Section: Microorganism Concentrationmentioning
confidence: 99%
“…Yang, Chen [78] found that with the addition of Fe 3+ , the rate and efficiency of jarosite bio-dissolution can be significantly accelerated and improved. Dong, Chong [81] explored the enhanced effect of biochar on the bioleaching of stone coal tailings by At. ferrooxidans.…”
Section: Microorganism Concentrationmentioning
confidence: 99%
“…Inspection results of underground water from coal mines in several places had shown that Thiobacillus ferrooxidans was one of the most pervasive bacteria in the mining area. 2,3 These bacteria are commonly used in bioleaching, 4,5 treatment of acid mineral wastewater, 6,7 and treatment of used circuit boards. 8,9 There are other bacteria such as Thiobacillus thiooxidans and Aspergillus niger , which could also recover metals through bioleaching.…”
Section: Introductionmentioning
confidence: 99%
“…Bioleaching is introduced as an environment-friendly method requiring less complexity and cost in operation [ 19 , 20 ], and can be an alternative to chemical extraction. In fact, vanadium has been recovered from industrial wastes such as stone coal [ 21 ], spent refinery catalysts [ 22 ], vanadium-bearing shale and slag fly ash through bioleaching process [ 23 , 24 ]. Chemolithotrophic bacteria, such as the Acidithiobacillus species, are well known for their use in metal bioleaching (e.g., copper, gold, and uranium) from ore deposits and mine tailings [ 25 ].…”
Section: Introductionmentioning
confidence: 99%